A influência das mensagens de texto na colaboração do tratamento ortodôntico com o uso de elásticos intermaxilares - Leone, Simone Maria Massud (2017)
The purpose of this prospective study was to evaluate the influence of text messages on the collaboration of orthodontic treatment with the use of intermaxillary elastics in Class II malocclusion. The sample consisted of 42 orthodontic patients with ages ranging from 14 to 34 years old, of both sexes (20 males and 22 females). These were randomly divided into two groups (control group) composed of 21 patients who did not receive messages and (Experimental group) composed of 21 patients who received a motivational and reminder text message. Messages were sent twice a week for a period of three months. Patients were instructed to wear the elastics all day, withdrawing only during meals and replacing them with new ones daily. All patients were instructed on the use and importance of the collaboration with intermaxillary elastics. The measurements were performed with a digital caliper in the plaster models, obtained at the beginning of the mechanical application with the elastics (T1) and three months after the beginning of the use of intermaxillary elastics (T2). For the intragroup and intergroup comparisons, between the T1 and T2 phases, the paired and independent t test were used, respectively. In all statistical tests a significance level of 5% was adopted. The results showed a statistically significant difference in the intra and intergroup comparisons between T1 and T2. Both groups presented a decrease in the measures from T1 to T2, showing the effectiveness of elastic use, however, in the experimental group, a 3-fold effect was observed. Thus, it was concluded that text messages had a positive influence on the motivation of patients regarding the use of intermaxillary elastics in the orthodontic treatment of Class II.